If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7 + 2) = x + -11 Combine like terms: 7 + 2 = 9 5(9) = x + -11 Multiply 5 * 9 45 = x + -11 Reorder the terms: 45 = -11 + x Solving 45 = -11 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 45 + -1x = -11 + x + -1x Combine like terms: x + -1x = 0 45 + -1x = -11 + 0 45 + -1x = -11 Add '-45' to each side of the equation. 45 + -45 + -1x = -11 + -45 Combine like terms: 45 + -45 = 0 0 + -1x = -11 + -45 -1x = -11 + -45 Combine like terms: -11 + -45 = -56 -1x = -56 Divide each side by '-1'. x = 56 Simplifying x = 56
| x-0.4=4.2 | | f(x)=ln(6x) | | 4x+5y+4=0 | | Cos(5x)-cos(3x)=0 | | .2x+13+x=-.10(x+40)+4 | | 10-3(3-2)=8 | | 42r^2=56-r | | (p+6)(p-2)=-7 | | x-1.2-2=-5 | | 144=[2x] | | 2r^2+19r=-24 | | 3s^2+8s=3 | | 3g-8(g-8)=42 | | log(3x+1)=1 | | 4d^5=10y | | log(3x+1)+6=7 | | 8x+9*0=72 | | 28+yi=21-x+7i | | 7x-5y=-21 | | x-1.2-2=5 | | -4(4x-3)=-5x+23 | | 252=k*2*36 | | (x+11)(2x+5)=117 | | z-57=-67 | | 1a+7+8a+1+2a+3a+2=218 | | 5x+3x+2x=84000 | | 7/10z-33/5=2/5 | | -6x+9+2x=49 | | 3(y-4)+2y=y-4 | | 500-500=500 | | 0.36=log(x) | | 0=3.5t^2-24t-140 |